Late-Onset Glaucoma-Filtrating Bleb Leak in a Penetrating Keratoplasty Patient: A Case Report - Zuleyha Yalniz-Akkaya; Ayse Burcu; Firdevs Ornek (Case Reports in Ophthalmological Medicine)
Introduction. Late-onset bleb leaks occur more frequently after the use of adjunctive antimetabolites and require surgical management to seal and preserve filtrating bleb. Case Presentation. A 48-year-old female presented with decreased visual acuity for five days in her left eye. She had a left penetrating keratoplasty one year earlier and two trabeculectomies 7 years earlier. Visual acuity was hand motions, intraocular pressure was 3 mmHg, corneal graft was clear, mature cataract was present, and axial length was 30.48 mm. The conjunctiva covering the superotemporal sclerotomy was avascular, flat, and partially lost. After heavily painting the bleb with a fluorescein, late-onset point leak was revealed. Overlying conjunctiva was excised. The atrophic, irregular, and partially absent scleral flap was covered by a processed human pericardium graft and conjunctival advancement. Postoperatively, intraocular pressure stabilized around 16 mmHg. After four months, phacoemulsification and intraocular lens implantation were performed. Visual acuity did not exceed 0.1 (in decimal notation) due to degenerative myopia-related macular atrophy. Corneal graft remained clear at her 6-month followup period. Conclusion. Surgical bleb revision using a pericardium graft and conjunctival advancement seems to be an effective method for treating late bleb leaks. However, careful follow-up is required for detecting recurrent leaks and elevated intraocular pressure.